Highly efficient and wide-color-gamut organic light-emitting devices using external microcavity. Issue 3 (3rd July 2019) - Mikami, Akiyoshi
Abstract : An external microcavity structure was introduced to the stacked cathode in organic light-emitting devices (OLEDs), and its influence on the luminescent characteristics was investigated. From the detailed optical analysis that was conducted, it was found that the surface plasmon loss in a metal cathode can be reduced to about one-fifth by using a semi-transparent thin-film cathode, and can be extracted outside through the microcavity effect after being converted to the thin-film waveguide mode. No less than 50% of the optical power in dipole emission was successfully utilized as the external and substrate modes. The luminous efficiency increased about 1.4-fold, and the color purity of the luminance also improved. As a trial preparation of red, green, and blue OLEDs with the external microcavity structure, the color gamut improved greatly and approached the BT.2020 national standard. The effect of the external microcavity will be discussed from the viewpoint of multi-scale optical analysis.